MILLENNIAL LECTURERS’ ATTITUDES IN INCORPORATING THE ONLINE APPLICATION IN THE EFL CLASSROOM - Angela Bayu Pertama Sari; Catharina Brameswari; Haya Haratikka (IKIP Siliwangi, 2020)
Millennial lecturers are considered to be proficient in teaching by making use of the technology in their classrooms. Nine millennial lecturers were involved in this study. It was carried out as qualitative research. The data collection technique was open-ended questionnaires then analyzed through thematic analysis. Three research questions were aimed to be examined. The first one was the investigation on the variety of the online applications used in the EFL classrooms; the second one was questioning about the lecturers’ attitudes in getting the benefits of online application, and the third one was observing the lecturers’ attitudes in overcoming the limitations that they found in incorporating the online application in the EFL classroom. The results showed that seventeen types of the online mobile application that were used by the nine millennial lecturers in this study. The millennial lecturers took advantage of the online applications by establishing communication, encouraging students’ self-study, improving the assessment, motivating the students, and improving the teaching instruction. Other result showed that they overcame the limitations of online mobile applications by giving more information and giving assignment to solve the learning management issues and also adjusting the learning when tools issues occur. Keywords: millennial, lecturer, online application, EFL